Les dépenses militaires soviétiques ou le fardeau de la défense soviétique - Jacobsen, Carl (Études internationales, 1986)
Our understanding of the Soviet defence burden remains woefully inadaquate. The official Soviet defence expenditure figure is not helpful. It is not inclusive. There is no concensus on what or how much is covered by other budget accounts. Soviet statistics do not allow independent calculation. Official Western estimates, on the other hand, are equally dubious. They reflect more on Western political dynamics than on Soviet reality. The Soviet defence industry is not immune from the vicissitudes of the economy at large. The Soviet military do not enjoy carte blanche. They contribute extensively to civilian needs, both in terms of goods and services. But, in turn, they extract benefits from a wide range of civilian endeavors. The military-political culture, rooted in an older Moscovy, and reinforced by Lenin's Clausewitzian leanings, is quite different from that which prevails in the west. There is no military-industrial complex threatening the Soviet State. In the USSR the military is OF the State, integral to a wider establishment. The military burden cannot be specified, for much is inextricably fused with the burden of State, and culture. It is systemic. It will be sustained. Because it is OF the System. Western debate is ethnocentric. We need new research, new under standing.